Information Spillovers in Experience Goods Competition - Chen, Zhuoqiong; Stanton, Christopher; Thomas, Catherine (Management Science, 2024)
Trialing an experience good allows consumers to learn their value for the sampled good and also informs beliefs about their value for similar products. These demand-side information spillovers across products create a relatively well-informed group of potential future consumers for rival firms. When both switching consumers and repeat buyers are profitable, firms face reduced incentives to set a low initial price to attract inexperienced consumers. Switchers and repeat buyers are more likely to be profitable in new product categories that build on major innovations and when firms can price discriminate based on purchasing history. We suggest that competing products and services arising from new innovations often have demand-side information spillovers from any product trial and are, hence, settings where competing firms can make overall profits even when selling products that consumers perceive to be indistinguishable prior to initial trial. This paper was accepted by Joshua Gans, business strategy. Funding: This work is supported by the National Natural Science Foundation of China (No. 71903046) and the “Shenzhen Peacock Program” (No. GA11409002). Supplemental Material: The e-companion is available at https://doi.org/10.1287/mnsc.2021.02754 .